2018
DOI: 10.1080/08820139.2018.1496098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Selenium on Oxidative Stress in Critically Ill Patients with Acute Respiratory Distress Syndrome

Abstract: Selenium restored the antioxidant capacity of the lungs, moderated the inflammatory responses, and meaningfully improved the respiratory mechanics. Despite these changes, it had no effect on the overall survival, the duration of mechanical ventilation, and ICU stay. Selenium can be used safely; however, more trials are essential to examine its clinical effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 33 publications
2
61
0
10
Order By: Relevance
“…Serum concentrations of IL-1β and IL-6 were inversely associated with serum Se concentrations. Nevertheless, there was no effect on overall survival, mechanical ventilation time, and length of stay in intensive care (176). In LPS-stressed RAW264.7 cells, LPS increased mRNA profiles of inflammatory genes, while short-time Se pretreatment reduced the LPS-induced upregulation of cyclooxygenase-2, intercellular adhesion molecule−1, IL-1β, IL-6, IL-10, nitric oxide synthase, and monocyte chemoattractant protein-1 and further increased expression of IFN-β and TNF-α (177).…”
Section: Seleniummentioning
confidence: 86%
“…Serum concentrations of IL-1β and IL-6 were inversely associated with serum Se concentrations. Nevertheless, there was no effect on overall survival, mechanical ventilation time, and length of stay in intensive care (176). In LPS-stressed RAW264.7 cells, LPS increased mRNA profiles of inflammatory genes, while short-time Se pretreatment reduced the LPS-induced upregulation of cyclooxygenase-2, intercellular adhesion molecule−1, IL-1β, IL-6, IL-10, nitric oxide synthase, and monocyte chemoattractant protein-1 and further increased expression of IFN-β and TNF-α (177).…”
Section: Seleniummentioning
confidence: 86%
“…Similarly, integrated-omics analyses of pathways affected by the selenium status in rectal biopsies from 22 healthy adults showed reduced inflammatory and immune responses and cytoskeleton remodeling in the suboptimal selenium status group [ 95 ]. Similarly, selenium supplementation was shown to modulate the inflammatory response in respiratory distress syndrome patients by restoring the antioxidant capacity of the lungs, which moderated the inflammatory responses through interleukin (IL)-1β and IL-6 levels and meaningfully improved the respiratory mechanics [ 96 ].…”
Section: Selenium and Immunobiologymentioning
confidence: 99%
“…38,39 This category (gray boxes) also includes interventions with indeterminate results, such as the case for positive end-expiratory pressure (PEEP) 15 -itself is a component of lung-protective ventilation, but the appropriate amount to use is still contended-or those that have value in ARDS patients aside from improving ARDS outcomes, such as early trophic enteral nutrition to prevent gastric intolerance 40 and extracorporeal membrane oxygenation as a rescue therapy. 35,36 In orange boxes are interventions that failed to demonstrate improvements in ARDS outcomes, such as antifungals, lisofylline, albuterol, simvastatin, vitamin C, and vitamin D. [41][42][43][44][45][46][47]76,77 Dexamethasone is also listed in this category given that the DEXA-ARDS trial was conducted in an unblinded fashion 28 and previous randomized trials showed no clinical efficacy for steroid administration in ARDS. Methylprednisolone, 27 rosuvastatin, 49 and omega-3 fatty acids, 48 listed in red boxes, have been shown to cause potential harm in randomized controlled trials.…”
Section: Prone Positioningmentioning
confidence: 99%